Development of STEM Learning based Android to Improving Students’ Logical Thinking Skills - Sri Setiawaty; Riska Imanda; Isna Rezkia Lukman; Ali Imron Pasaribu (Postgraduate, University of Mataram, 2022)
This study aims to determine the feasibility of STEM learning based Android that was developed to increase students' logical thinking skills competence, as well as to determine student readiness with the renewal of learning modes and student responses to the developed learning media. This study uses the type of Research and Development (R&D) research with adapted from Borg & Gall (2007) dan 4-D model procedural. The learning media product being developed in the form of an android application with a STEM approach on Chemistry Science material. The android application used in this research is the Smart App Creator software. The validity of the media and the quality of the learning media developed obtained the results of an assessment are 93% and 92% (Very Good), then received a positive response from students is 90%, Furthermore the media was developed should be improve logical thinking skills and significantly with a comparison of the average value of the pretest score of 27.04 and posttest of 73.5 to learning outcomes.